2022
DOI: 10.1038/s41467-022-32026-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning southern corn rust resistant gene RppK and its cognate gene AvrRppK from Puccinia polysora

Abstract: Broad-spectrum resistance has great values for crop breeding. However, its mechanisms are largely unknown. Here, we report the cloning of a maize NLR gene, RppK, for resistance against southern corn rust (SCR) and its cognate Avr gene, AvrRppK, from Puccinia polysora (the causal pathogen of SCR). The AvrRppK gene has no sequence variation in all examined isolates. It has high expression level during infection and can suppress pattern-triggered immunity (PTI). Further, the introgression of RppK into maize inbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…In the hybrid panel, three candidate loci were detected by association analysis with additive and dominant coding ( Figures 3C, E and Table 3 ), two of them were different, which suggested that the dominant effect is also very important in the breeding of rust-resistant hybrids. In all association analyses for 2 populations, a highly significant locus was detected on chromosome 10, which tight chained with the known SCR resistance gene RppC ( Deng et al., 2022 ) and other reported QTL, including RppQ ( Chen et al., 2004 ), RppD ( Zhang et al., 2009 ), RppS/RppK ( Wu et al., 2015 ; Chen et al., 2022 ), RppM ( Wang et al., 2020 ). The stability and significant effect of this loci suggested that MAS can be used to fix this region to the germplasm in the breeding process.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the hybrid panel, three candidate loci were detected by association analysis with additive and dominant coding ( Figures 3C, E and Table 3 ), two of them were different, which suggested that the dominant effect is also very important in the breeding of rust-resistant hybrids. In all association analyses for 2 populations, a highly significant locus was detected on chromosome 10, which tight chained with the known SCR resistance gene RppC ( Deng et al., 2022 ) and other reported QTL, including RppQ ( Chen et al., 2004 ), RppD ( Zhang et al., 2009 ), RppS/RppK ( Wu et al., 2015 ; Chen et al., 2022 ), RppM ( Wang et al., 2020 ). The stability and significant effect of this loci suggested that MAS can be used to fix this region to the germplasm in the breeding process.…”
Section: Discussionmentioning
confidence: 76%
“…It is noteworthy that Rpp9 is closely linked, with a genetic distance of 1.5 cM, to a common rust resistance gene rp1 , but its genomic location had not been confirmed ( Ullstrup, 1965 ). In recent years, more resistance loci on chromosome 10 have been detected, including RppP25 ( Liu et al., 2003 ), RppQ ( Chen et al., 2004 ), RppD ( Zhang et al., 2009 ), RppC ( Yao et al., 2013 ), Rpp12 ( Zhang, 2013 ), RppS ( Wu et al., 2015 ), RppM ( Wang et al., 2020 ), qSCR6.01 ( Lu et al., 2020 ), RppCML496 ( Lv et al., 2021 ), RppK ( Chen et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…S8). The firefly Luciferase (LUC) reporter gene system has been a powerful tool to monitor the cell viability through quantifying the fluorescence activity in many studies [ 47 50 ]. Here, we also co-expressed the candidate proteins and LUC to perform the cell death assay.…”
Section: Resultsmentioning
confidence: 99%
“…In maize, several resistance QTLs were detected in two resistant lines CML496 and K22 against southern corn rust (SCR). Two major QTLs, RppCML496 and RppK , accounted for 43–78% and 68% of phenotypic variation, respectively (Lv et al, 2021; Chen et al, 2022; Deng et al, 2022). Further studies have indicated that the causative genes RppC and RppK of these two major QTLs encode NLR proteins.…”
Section: Nlr‐conferred Qdrmentioning
confidence: 99%
“…Further studies have indicated that the causative genes RppC and RppK of these two major QTLs encode NLR proteins. RppC and RppK could perceive their cognate effectors AvrRppC and AvrRppK, respectively, to elicit defense responses (Chen et al, 2022; Deng et al, 2022), and the genetic variation of AvrRppC determines RppC resistance against SCR (Deng et al, 2022). In addition, the maize NLR gene Rcg1 confers QDR to anthracnose stalk rot in maize (Broglie et al, 2006).…”
Section: Nlr‐conferred Qdrmentioning
confidence: 99%